Magnesium–Air Battery with Increased Power Using Commercial Alloy Anodes - Andrey Zhuk; Grigory Belyaev; Tatiana Borodina; Elena Kiseleva; Eugeny Shkolnikov; Viktor Tuganov; Georgy Valiano; Viktor Zakharov (Energies, 2024)
Mg–air batteries have high theoretical energy density and cell voltage. Their use of environmentally friendly salt electrolyte and commercially available magnesium materials determines their acceptable technical and economic efficiency, safety, and ease of operation. However, the practical applicationsof Mg–air batteries arevery limited due to the polarization of magnesium anodes and the batteries’ low Faraday efficiency. In this study, we considered the possibility of designingan Mg–air battery withincreased power by adapting engineering solutions developed for an Al–air battery with alkaline electrolytes. To increase the specific power of the battery, it was proposed that the internal resistance of the battery maybe reduced using a concentrated salt electrolyte. We investigated the discharge performance of a commercial alloy of AZ31 type in 15 wt.% NaCl electrolyte at current densities of 40–120 mA/cm2. The influence of a small addition of sulfosalicylic acid into the electrolyte on the discharge performance of the anode alloy was studied as well. The estimated values of the energy characteristics of the 0.5 kW Mg–air battery were compared with those of an Al–air battery with an alkaline electrolyte.